2022
DOI: 10.1002/pro.4501
|View full text |Cite
|
Sign up to set email alerts
|

Design of a H2O2‐generating P450SPα fusion protein for high yield fatty acid conversion

Abstract: Sphingomonas paucimobilis' P450SPα (CYP152B1) is a good candidate as industrial biocatalyst. This enzyme is able to use hydrogen peroxide as unique cofactor to catalyze the fatty acids conversion to α‐hydroxy fatty acids, thus avoiding the use of expensive electron‐donor(s) and redox partner(s). Nevertheless, the toxicity of exogenous H2O2 toward proteins and cells often results in the failure of the reaction scale‐up when it is directly added as co‐substrate. In order to bypass this problem, we designed a H2O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(29 citation statements)
references
References 61 publications
2
27
0
Order By: Relevance
“…To this end, we have recently demonstrated that the use of MSOX in a chimeric system is beneficial for the catalytic activity as it provides H 2 O 2 in a controlled manner and it prevents the rapid degradation of the heme. [ 37 ] Moreover, in the latter chimeric system the catalytic activity of MSOX was comparable to the ones previously reported in the literature. [ 34 ] Indeed, several studies have shown how the catalytic activity of a P450 domain can be modulated by creating functional self‐sufficient fusion proteins via the so‐called “Molecular Lego” approach.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…To this end, we have recently demonstrated that the use of MSOX in a chimeric system is beneficial for the catalytic activity as it provides H 2 O 2 in a controlled manner and it prevents the rapid degradation of the heme. [ 37 ] Moreover, in the latter chimeric system the catalytic activity of MSOX was comparable to the ones previously reported in the literature. [ 34 ] Indeed, several studies have shown how the catalytic activity of a P450 domain can be modulated by creating functional self‐sufficient fusion proteins via the so‐called “Molecular Lego” approach.…”
Section: Discussionsupporting
confidence: 83%
“…To this end, we have recently demonstrated that the use of MSOX in a chimeric system is beneficial for the catalytic activity as it provides H 2 O 2 in a controlled manner and it prevents the rapid degradation of the heme. [37] Moreover, in the latter chimeric TA B L E 1 Kinetic properties of CYP116B using NADPH and NADH as reductants and cytochrome c as electron acceptor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured the accumulation of H 2 O 2 in real time coupling the CYP116B5-SOX reaction to the horseradish peroxidase activity, which uses H 2 O 2 to convert ABTS into a colored product (ABTS• + ) (Figure S4). [43,55] The data indicate that the CYP116B5-SOX produced 1.308 mM ± 0.038 mM after 5 min of reaction, that is the time used in our experiment to extrapolate the kinetics parameter for the conversion of p-nitrophenol, and up to 3.650 ± 0.136 mM over 20 min.…”
Section: Hydrogen Peroxide Production During Cyp116b5-sox Reactionmentioning
confidence: 76%
“…Important improvements can stem from protein engineering and creation of chimeric enzymes based on the modular combination called "Molecular Lego", which has already successfully employed BMR as a fused module to different enzymes. [35][36][37][38][39][40]88,89] AUTHOR CONTRIBUTIONS Conceptualization: Francesca Valetti; Gianluca Catucci; Sheila J.…”
Section: Systemmentioning
confidence: 99%